Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1021/acs.analchem.1c00093
|View full text |Cite
|
Sign up to set email alerts
|

General Strategy for Bioluminescence Sensing of Peptidase Activity In Vivo Based on Tumor-Targeting Probiotic

Abstract: The abnormally expressed peptidases in human tissues are associated with many kinds of cancers. Monitoring of endogenous peptidase activity could allow us for pathophysiology elucidation and early clinical diagnosis. Herein, we developed a general strategy for bioluminescence (BL) sensing of peptidase activity in vivo based on tumor-targeting probiotics. The probiotic that harbored a luciferase-encoding plasmid was used to target and colonize tumor and provide luciferase for BL imaging. The peptide-based probe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Necrosis is commonly found in the advanced stages of a solid tumor when the size of the tumor was relatively large . Therefore, EcN localized well in large tumors . To verify the colonization ability of PCB, relatively smaller tumors were used in this experiment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Necrosis is commonly found in the advanced stages of a solid tumor when the size of the tumor was relatively large . Therefore, EcN localized well in large tumors . To verify the colonization ability of PCB, relatively smaller tumors were used in this experiment.…”
Section: Resultsmentioning
confidence: 99%
“…39 Therefore, EcN localized well in large tumors. 40 To verify the colonization ability of PCB, relatively smaller tumors were used in this experiment. In vivo colonization of PCB was imaged by using D-luciferin.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…During tumor autophagy, these two compounds are cleaved by their corresponding autophagy enzymes to yield d -Cys and CBT, respectively, which undergo a CBT-Cys click reaction to yield d -aminoluciferin inside cancer cells, turning tumor BL “on”. In fact, this in situ luciferin formation approach has been successfully applied for dual-analyte imaging in inflammation and tumor mice models. , And in this study, we found it was also well-performed in precise cancer autophagy BL imaging.…”
Section: Introductionmentioning
confidence: 99%
“…The existence of bacteria in solid tumors has been well-documented for a long time. Bacteria have gained unprecedented attention due to their unique capabilities, such as intratumoral selective colonization, and as vectors for delivering prodrug-converting enzymes. Anaerobic bacteria can penetrate and proliferate in the hypoxic regions of tumors. Recently, many studies have reported that the number of bacteria accumulated and proliferated in tumor cells might be 1000× higher than that in reticuloendothelial organs . More importantly, bacteria are easily eliminated by antibiotics in normal tissues, allowing them to play important roles in cancer diagnosis and treatment.…”
Section: Introductionmentioning
confidence: 99%
“…40−42 Recently, many studies have reported that the number of bacteria accumulated and proliferated in tumor cells might be 1000× higher than that in reticuloendothelial organs. 43 More importantly, bacteria are easily eliminated by antibiotics in normal tissues, allowing them to play important roles in cancer diagnosis and treatment. Compared with other attenuated tumor-targeting pathogenic bacteria, the facultative anaerobic probiotic Escherichia coli Nissle 1917 (EcN) has a superior ability to target and colonize in tumor tissues without pathogenicity.…”
Section: ■ Introductionmentioning
confidence: 99%